Does maternal nutrition in pregnancy and birth weight influence levels of CHD risk factors in adult life? - Huxley, R; Neil, H (2004)
The fetal-origins hypothesis suggests that maternal and fetal nutrition can have a profound and sustained impact on the health of the offspring in adult life. Although there is abundant literature reporting on the associations between birth weight and disease risk factors, only a handful of studies have been able to examine the relationship between maternal nutrition in pregnancy with the health of offspring in adult life directly. Between 1942 and 1944, nearly 400 pregnant women were recruited into a dietary study to determine whether the wartime dietary rations were sufficient to prevent nutritional deficiencies. Detailed biochemical and clinical assessments were conducted for each of the women, who were followed-up until after delivery. More than 50 years later, approximately one-quarter of the adult offspring were recruited into a study to explore the possible impact of maternal nutrition in pregnancy on CHD risk factors, including glucose tolerance, blood pressure and components of the lipid profile. Results from the present study provide no evidence to support the hypothesis that birth weight or maternal nutrition in pregnancy are associated with CHD risk factors in adult life.